PEMANFAATAN MINYAK Dryobalanops aromatica Gaertn SEBAGAI BAHAN PEWANGI ALAMI - Gunawan Pasaribu; Gusmailina; Sri Komarayati (BRIN Publishing, 2014)
Dryobalanops aromatica Gaertn is a woody plant that produce oil and crystal which has high economical value. Currently oil and crystals becomes an export commodity for cosmetics and pharmaceuticals purposes. In the community, oil utilization is still limited for simple medication in various minor ailments. Utilization in domestic area is still very limited, thust it is necessary to conduct research that lead to increase additional value of the oil. Utilization as fragrance materials/perfume is expected to increase the added value. Result showed, the preferred perfume formula is that with formulation of Dryobalanops oil (25%), ethanol (75%) and green tea additives as odorant, PG and patchoulioil (0.8%). The characteristics of formula have a soft fragrance level, with sharpness level at rather sharp fragrance. Dryobalanops aromatica oil has borneol as marker compounds. And the other chemical compound, such as Caryophyllene; 3-Cyclohexene-1-methanol, .alpha., .alpha., 4-trimethyl-, (S)- (CAS) p-Menth-1-en-8-ol, (S)-(-)-; 1,4, 7-Cycloundecatriene, 1,5,9,9-tetramethyl-, Z,Z,Z- dan 3-Cyclohexen-1-ol, 4-methyl-1-(1-methylethyl)- (CAS) 4-Terpineol.